Hyperoside ameliorates lupus nephritis by suppressing AKT1-mediated PANoptosis in podocytes: integrating network pharmacology and experimental validation - Cheng, Lili; Tang, Zhongfu; Li, Ming; Huang, Chuanbing (Frontiers in Pharmacology, 2026)
BackgroundLupus nephritis (LN), one of the most common and severe complications of systemic lupus erythematosus (SLE), remains challenging to treat due to its complex pathogenesis. Hyperoside (Hyp), a naturally occurring flavonol glycoside and a key active component in numerous Chinese medicines and herbs, has demonstrated renoprotective effects via multiple signaling pathways, showing promise for LN treatment. However, its underlying mechanisms of renal protection in LN, particularly its regulatory potential on PANoptosis, remain unexplored.ObjectiveThis study investigated the role of PANoptosis in LN pathogenesis, focusing on protein kinase B (AKT1) -mediated podocyte PANoptosis, to elucidate the therapeutic mechanism of Hyp.MethodsPotential Hyp targets were predicted using the SwissTargetPrediction database, while LN-related targets were retrieved from the GeneCards database. Overlapping targets were identified as potential key targets, and a Protein-Protein Interaction (PPI) network was constructed to screen core targets. GO and KEGG analyses of these overlapping targets were performed via the DAVID database to predict the mechanisms of Hyp against LN. Molecular docking between Hyp and the core target was conducted using AutoDock (Version 1.5.7) and visualized with PyMOL. Finally, in vivo and in vitro experiments, including H&E staining, TUNEL staining, immunofluorescence, flow cytometry, Western blotting, immunohistochemistry, and PCR, were performed to assess renal pathology, cell death, and the mRNA/protein expression levels of key targets and PANoptosis markers.ResultsNetwork pharmacology and molecular docking analyses indicated that AKT1 is a core target shared by Hyp and LN, with Hyp exhibiting stable binding to AKT1. Experimental validation demonstrated that Hyp treatment inhibited podocyte PANoptosis and alleviated renal injury in MRL/lpr mice. Mechanistically, Hyp suppressed PANoptosis by modulating the PI3K/AKT axis. AKT1 overexpression attenuated the therapeutic effects of Hyp, confirming its pivotal role in LN pathogenesis.ConclusionThis study reveals that AKT1-mediated podocyte PANoptosis is a key mechanism in LN and establishes Hyp as a promising therapeutic agent targeting this pathway. These findings provide a novel and clinically translatable strategy for LN treatment.